Inhibition of hotspot formation by alumina addition in flash sintering of (La0.2Nd0.2Sm0.2Eu0.2Gd0.2)2Zr2O7 high-entropy ceramic. Issue 15 (December 2022) - Sun, Yu; Mao, Hai-Rong; Shen, Ping
Abstract: Sintering inhomogeneities caused by hotspots are one of the factors hindering the development of flash sintering technology. Herein, to overcome this problem for a high-entropy pyrochlore-structured (La0.2 Nd0.2 Sm0.2 Eu0.2 Gd0.2 )2 Zr2 O7 ceramic (abbreviated as RE2 Zr2 O7 ), we propose a simple strategy, namely, addition of Al2 O3 to the ceramic and achieved a significant effect. During flash sintering, rare earth ions in RE2 Zr2 O7 reacted with Al2 O3 to form REAlO3 and RE2−x Zr2 O7–3x/2, which substantially improved the sintering homogeneity. With an increase in the Al2 O3 content, REAlO3 transformed into REAl11 O18 . The crack deflection and bridging effect caused by the formation of these phases and their intrinsic high hardness and high modulus improved the mechanical properties of the composite ceramic. The use of an internal reaction to improve the electrical conductivity of a ceramic body is an economical and effective strategy to prevent hotspot formation during flash sintering.